Effect of the Different Shapes of Air Diffuser on Oxygen Mass Transfer Coefficients in Microporous Aeration Systems. (2016) - Cheng, Xiangju; Xie, Yuning; Zheng, Huaiqiu; Yang, Qian; Zhu, Dantong; Xie, Jun
Abstract: It is common to apply aeration facility in lakes, rivers, estuaries and ponds where the dissolved oxygen concentration needs to be increased. Among sufficient aeration facilities, the microporous aeration systems, with advantaged energy-saving, environmental protection, easy installation, adaptability and other good characteristics, are popular for aquaculture ponds or aeration tank in sewage treatment plant. A microporous aeration system mainly includes an air compressor, air diffuser and air supply line to connect air compressor and air diffuser, where air diffuser is often empirically a disc rolled up by a length of aeration tube. In fact, what kind of shape rolled up by the length of aeration tube is still an open question for optimal oxygen mass transfer coefficient. So a series of re-oxygenation experiments were attempted under different shapes of air diffuser rolled up by a same length of aeration tube in laboratory. The shapes were I-shape, C-shape, S-shape and Disc-shape. The experimental apparatus mainly includes one glass tank, a microporous aeration system and a dissolved oxygen meter. The sizes of the glass tank were 2 m × 0.8 m × 0.8m (length × width × height). The different shapes of air diffuser were fixed in the center of the tank bottom. The diffused-air flow rate was set among 0.6-1.8m 3 /h and the water depth was set of 0.4 m, 0.55m, 0.7m. Based on the Standard Test Method for Oxygen from American Society of Civil Engineers (ASCE), the oxygen volumetric mass transfer coefficients were calculated. The results showed that the optimal aeration efficiency is under the use of I-shaped diffuser, and then C-shaped and disc-shaped diffuser, the poorest one is the use of S-shape. When the air-free water surface mass transfer was cut off by covering plastics film on the top of the tank, the oxygen volumetric mass transfer coefficients of I-shaped, C-shaped, S-shaped and disc-shaped diffusers were decreased. The best aeration performance is I-shape, the poorest one is S-shape.